Metabolite Profile and Antioxidant Capacity of Centella asiatica Leaves Extract with Different Extraction Methods - Wildayati, Wildayati; Suparto, Irma Herawati; Rafi, Mohamad (al Kimiya: Jurnal Ilmu Kimia dan Terapan, 2024)
Centella asiatica known as pegagan in Indonesia, belongs to the Apiaceae family and is widely used as salad, cosmetics ingredients, and herbal medicine for improving memory. This research aimed to determine the total phenolics content (TPC), antioxidant capacity (AC), and FTIR spectrum of C. asiatica leaves extracts using different extraction methods. C. asiatica extracts were prepared using maceration, reflux, and ultrasonication. The Folin-Ciocalteu method was used to determine TPC, and we found a higher level of TPC when using maceration, about 9,96 ± 0,20 mg GAE g-1 dry powder. Antioxidant capacity from the three extracts was measured using DPPH and FRAP methods. The highest antioxidant capacity using DPPH and FRAP methods was found in C. asiatica leaves extract using maceration with a value of 29,60 ± 0,71 and 14,04 ± 0,38 ????mol TE g-1 dry powder, respectively. The FTIR spectrum of each extract indicates the presence of vibration from several functional groups such as O-H, C-H, and C=C, likely from phenolics and C-O. The pattern of FTIR spectrum from the three C. asiatica leaves extracts gives different spectrum profiles and characteristics. Principal component analysis using FTIR spectrum data shows good clustering for each extract with 89% data variability (PC1 77% and PC2 12%). It can be concluded that TPC, AC, and FTIR spectrum profiles are different when using different extraction methods.